EARLY-AGE MARRIAGE DURING THE COVID-19 PANDEMIC IN INDONESIA: 2020-2021 KATADATA ANALYSIS - Novita Rina Antarsih; Yulia Sari; Sri Sukamti; Rosni Lubis (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
Early marriage is marriage at the age of less than 18 years. Child marriage in Indonesia is still high, and maternal and infant deaths are caused by pregnancy and childbirth. There is no picture of early marriage during the COVID-19 pandemic in Indonesia. This study aims to describe the incidence of early marriage during the COVID-19 pandemic. This type of research uses a narrative approach with a literature review using articles related to early marriage and secondary data from infographic data. Results: Indonesia is one of the countries with the most active cases of COVID-19. The highest number of married girls is in South Kalimantan Province. The dispensation for child marriage in 2020 has tripled from 2019 and is still high in 2021. Indonesian children who marry for the first time are under 15 years old. Girls marry earlier than boys, followed by 1 million teenage pregnancies and four million births in Indonesia. Conclusion: Indonesia is one of the countries with the most active COVID-19 cases in the world, and there has been an increase in cases of early marriage due to applications for child marriages from the lower class, as well as an increase in pregnancies and childbirth.